Environmental and cost efficiency of steam-powered electricity generation in Iran - Lahiji, Foroogh Shadman (2012)
During the past two decades, environmental side effects of economic activities have become the central part of public and political discussions. An effective energy policy should encourage the different enterprises, utility companies and individuals to utilize energy efficiently and in more environmental friendly processes, technologies, and materials. Fossil fuels are responsible for the large amount of human-related air pollution in Iran. Due to the fact that more than 45.4% of Iranian electricity is produced by steam plants which are applying fossil fuel, fuel choices play the most important role at national and even international levels. Among the fossil fuels, natural gas plays the most important role in Iran’s fuel-fired generating system and is the preferred fuel due to its cleaner combustion characteristics compared to other fuels. Since few researches had examined the environmental and economic tradeoffs among the different fuels, this study estimates the contribution of gas, fuel oil and gas oil inputs and compare it with an alternative substitute (LNG) to illustrate the best available environmental and economical choice for the largest electricity generation sector in Iran. To minimize SO2 emissions and costs, the study applies a Data Envelopment Analysis followed by Charnes, Cooper and Rhodes (CCR) and then DEA-MBP followed by Coelli et al., 2005 that incorporates the material balance principle (DEA-MBP) in the first stage of the analysis. Findings are evident that by switching to natural gas, the substantial increase (nearly 80%) in environmental efficiency and cost efficiency (nearly 30%) would result while the technical efficiency would demonstrate a nearly 7% decrease. Therefore, results highlight the positive impact of fuel switching on Cost and Environmental efficiency scores respectively. By considering the investment pay-back, the study indicated that small-sized power companies are not considered economical to switch to mini LNG. In the second stage of our analysis, the Ordinary Least Square (OLS) estimator were employed to extract the missing factors in the first stage by regressing the technical, cost and environmental efficiency scores derived from the DEA on the explanatory variables (age, size, fuel type and year of observation) which could influence the efficiency levels of the steam plants in Iran which may not have been considered in the first stage analysis. The study provides a comprehensive efficiency analysis of specific applications of steam power plants in Iran to serve the applied strategy to the component stakeholders for doing policy implication. The results clearly demonstrate that by switching to natural gas and instructing medium and large size plants instead of small ones, the environmental efficiency would increase dramatically and the cost efficiency also would indicate an increase while the technical efficiency demonstrates little decrease. Therefore, being aware of the tradeoffs for individual and also public policy makers seems necessary. Furthermore, it would be mostly valuable to indicate what changes would be necessary to increase the efficiency of the most inefficient plants to the level of their efficient peers. Thus, considering new incentive systems seems reasonable to encourage the best fuel resources and other factors which simultaneously fulfill the desire for cost and environmental efficiency especially sulfur reduction.